Long‐term effect of first‐line injectable multiple sclerosis treatments: Input of a time‐dependent propensity score. Issue 12 (11th November 2020) - Lefort, Mathilde; Foucher, Yohann; Lenain, Remi; Vukusic, Sandra; Edan, Gilles; Leray, Emmanuelle
Abstract: Purpose: The long‐term effect of beta‐interferon and glatiramer acetate on multiple sclerosis (MS) disability progression has resulted in controversial results, probably due to a lack of appropriate control of biases as raised in observational studies. In particular, the time of the therapeutic decision is difficult to define when the controls are not treated. Methods: This retrospective observational study was based on a series of patients from the MS expert center in Rennes, France. We used a time‐dependent propensity score defined as the linear predictor of a Cox model estimating the hazard of being treated at each time from MS onset. The matching procedure resulted in two groups: patients matched as treated and as not yet treated. The restricted mean times (RMST) to reach a moderate level of disability or worsening of the disability were compared between the two groups in an intention‐to‐treat analysis. Results: Of the 2383 patients included in the study, 556 were matched as treated. The matching procedure provided a good balance of both the time‐fixed and the time‐dependent covariates. A slight difference was observed for the time to reach a moderate level of disability, in favor of the "not yet treated" group (difference in the RMST: −0.62 [−0.91; −0.33]) while no difference was found in terms of worsening of the disability (−0.03 [−0.24; 0.33]). Conclusion: This unexpected result is probably due to unmeasured confounders. However, this time‐dependent PS warrants consideration in long‐term effectiveness studies.